SIMULASI UJIAN PERSIAPAN TOEFL BERBASIS WEB DENGAN MENGGUNAKAN METODE INCREMENTAL PROCESS MODEL - Rudi Kurniawan (Journal of Information Technology, 2022)
The Test of English as a Foreign Language (TOEFL) is an exam or test that measures a person's English ability. This test tests listening, structure, and reading skills. For STMIK "AMIKBANDUNG" students, the TOEFL test is a requirement that must be followed as a competency certificate requirement for student graduation (final trial). Currently, participants are taking the test from a third party and have to pay exam administration fees and spend time studying, which may not guarantee that they will achieve the set score. As an alternative solution, we need a learning tool that saves space, saves time, and saves costs. Developing learning media and website-based TOEFL preparation exam simulations is an option. This designed website is capable of providing a TOEFL preparation test simulation like the actual TOEFL exam that will be faced. The system development method uses the Incremental Process Model method, where this method focuses on delivering operational products in each increment which is a stripped-down version of the final product, but the product provides the ability to serve users. This website-based application can be used by the general public as a means of simulating the TOEFL test. From the test results, the website built has been able to provide a TOEFL simulation for prospective test takers. This website is online and free, so it can make it easier for users to find out how many TOEFL scores they get. Keywords— TOEFL simulation, Incremental Process Model, web-based TOEFL, TOEFL Preparation, STMIK AMIK BANDUNG